Análisis del tarifario eléctrico en el sector Guasmo Sur Cooperativa Florida II Guayaquil, 2013-2018 - Dávila Ganchozo, José Rafael (2021)
The thesis, the report of which is presented, is the result of the research process developed in view of the problem of the impact of Guayaquil's electricity tariff deficit, on the sustainability of the future of this energy sector, due to the misuse of this resource by users in the Guasmo Sur Cooperative Florida II, 2013-2018. From this, the objective of analyzing the electricity tariff in the sector and period referred to was set out. Through a theoretical systematization from development theories and conceptual and legal references, a mixed approach methodology, exploratory and descriptive, was followed, with the application of a survey to the family representatives defined by the sample, which offered valuable information about the problem that was also corroborated. ……….